Rapid emergence of colistin resistance and its impact on fatality among healthcare-associated infections. Issue 3 (March 2018) - Aydın, M.; Ergönül, Ö.; Azap, A.; Bilgin, H.; Aydın, G.; Çavuş, S.A.; Demiroğlu, Y.Z.; Alışkan, H.E.; Memikoğlu, O.; Menekşe, Ş.; Kaya, Ş.; Demir, N.A.; et al.
Summary: This article describes the emergence of resistance and predictors of fatality for 1556 cases of healthcare-associated Gram-negative bloodstream infection in 2014 and 2015. The colistin resistance rate in Klebsiella pneumoniae was 16.1%, compared with 6% in 2013. In total, 660 (42.4%) cases were fatal. The highest fatality rate was among patients with Acinetobacter baumannii bacteraemia (58%), followed by Pseudomonas aeruginosa (45%), Klebsiella pneumoniae (41%), Enterobacter cloacae (32%) and Escherichia coli (28%). On multi-variate analysis, the minimum inhibitory concentrations for carbapenems [odds ratio (OR) 1.02, 95% confidence interval (CI) 1.01–1.04; P  = 0.002] and colistin (OR 1.1, 95% CI 1.03–1.17; P  = 0.001) were found to be significantly associated with fatality.